The Evolution of Electronic Marketplaces: an exploratory study of internet-based electronic within the American Independent Insurance Agency system - Burton, Andrew; Mooney, John (Australasian Journal of Information Systems, 1998)
Evolving competitive, organisational and technology environments drive organisations to continually evaluate how information technology resources can be exploited for competitive value. The emergence of a global information infrastructure has spawned an entirely new area for competitive exploitation, electronic marketplaces. This paper first presents a review and synthesis of the conceptual and empirical literature on electronic marketplaces. Drawing upon multiple theoretical perspectives, we develop a framework for analysing their potential influences on market and industry structure. This conceptual framework is then applied to an empirical assessment of the potential of the Internet as an electronic marketplace for the American Independent Insurance Agency System.